What is the level of information technology maturity in Ontario’s long-term care homes? A cross-sectional survey study protocol - Clare Liddy; Sathya Karunananthan; Gregory Alexander; Mohamed Gazarin; Peter Tanuseputro; Amy T Hsu; Ramtin Hakimjavadi; Celeste Fung; Deanne Houghton; James LaPlante; Cheryl Levi (BMJ Open)
Introduction The number of Canadians 75 years and older is expected to double over the next 20 years, putting continuing care systems such as long-term care (LTC) homes under increasing pressure. Health information technology (IT) has been found to improve the quality, safety and efficiency of care in numerous clinical settings and could help optimise LTC for residents. However, the level of health IT adoption in Ontario’s LTC homes is unknown and, as a result, requires an accurate assessment to provide a baseline understanding for future planning.Methods and analysis We will use a cross-sectional design to investigate the level of IT maturity in Ontario’s LTC homes. IT maturity will be assessed with the LTC IT Maturity Instrument, a validated survey examining IT capabilities, the extent of IT use and degree of internal/external IT integration across the domains of resident care, clinical support and administrative activities. All LTC homes in Ontario will be invited to participate. The Director of Care for each home will be directly contacted for recruitment. The survey will be distributed online (or by paper, if preferred) to LTC homes and completed by a staff member designated by the LTC to be knowledgeable about its IT systems. Analyses will consist of descriptive statistics characterising IT maturity across LTC homes and inferential statistics to examine the association between key facility-level characteristics (size, ownership, rurality) and IT maturity.Ethics and dissemination This study was reviewed by the Ottawa Health Science Network Research Ethics Board and was exempt from full ethics review. Findings will be disseminated through peer-reviewed publication and presentations to the scientific community and stakeholders. Dissemination of our findings will not only inform provincial planning for harnessing the potential of technology in LTC but may also enable quality improvement initiatives in individual LTC homes.